Spillover effects of labour market reforms in a three-country world - Claudia Fries (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
I extend the model-based literature on spillover effects of labour market reforms on foreign (un-)employment by allowing for third-country effects. When the workhorse two-country model is enlarged to include a third country, a reform causes an additional indirect effect through a terms-of-trade shift between the foreign countries. To quantify the increase or reduction in the overall spillover by means of this channel, simulations based on empirically realistic scenarios are carried out. Thereby, the indirect effect turns out to be too small to overturn the direct effect or to increase it considerably. Differences in the reform spillover effects between foreign countries are mainly due to differences in characteristics which influence the size of the direct impact.
urn:nbn:de:bsz:180-madoc-394707
Keywords: E24; F42; 330; spillover; labour market reforms; third-country effects; indirect effects; dynamic general equilibrium models